Towards the solutions for solving the content-type challenge of OTRmail extension for thunderbird - Ng, Kang Le. (2011)
In email communication, there is always the threat of the email content being compromised as simple emails are being sent by plain text. Solutions like PGP and S/MIME are available to solve the threat. However, those solutions are too complex, making it not practical and thus deterring users from using them. This task of this project is to deal with the OTRmail Extension, serving as a platform to support the OTRmail Protocol on Thunderbird. However, the current development of the extension has met with a problem to modify the content type of the email to the extension’s requirement. The main aim of the project is to explore the different possible ways to alter an email’s content type through Thunderbird and successfully implement it to the OTRmail extension.